Application of AI in Sustainable Teaching and Learning - Gupta, Aarti Dwaraka Prasad (Journal of Advanced Research in Applied Artificial Intelligence and Neural Network, 2021)
Technology today has crossed all its restrictive barriers and has become a helping-hand to all the people of different walks of life. Artificial Intelligence has become a new wave of the growing technology in the world. Not only artificial intelligence has helped in creating amazing robots, but also it has paved its way to teaching and learning. This paper aims to highlight the importance and emergence of using artificial intelligence in today’s education system. How the effective applications of artificial intelligence affect the current teaching and learning and why it is more effective than the current technologies used for teaching in schools is all explained here. How to cite this article: Gupta ADP. Application of AI in Sustainable Teaching and Learning. J Adv Res Appl Arti Intel Neural Netw 2020; 4(1): 17-20.